ENTERTAINMENT CONTENT OF THE YOUTUBE CHANNEL IN WAR'S CONDITIONS: PROSPECTS AND EXPEDIENCY - Nina Vernyhora; Kateryna Balabanova; Olha Mykhalchenko; Dmytro Chelyshev (Інтегровані комунікації)
The article analyzes the impact of entertainment content on the psychology of citizens of a country at war. The challenges the authors of Ukrainian YouTube channels face are described, and the trends that should be followed to be heard are listed. The article emphasizes the adaptation of video content to the unfavorable conditions that have developed in our country and the importance of developing the Ukrainian-language segment on the YouTube platform.